Clinical significance and pro-oncogenic function of DBF4 in clear cell renal cell carcinoma - Liuyan Chen; Lvying Wu; Minying Tang; Yuanhang Cheng; Kuanyin Wang; Jianan Zhang; Wenyi Deng; Lingfeng Zhu; Jin Chen (BMC Urology)
Abstract Background Clear cell renal cell carcinoma (ccRCC) is the most common malignant urological tumor, and regrettably, and is insensitive to chemotherapy and radiotherapy, resulting in poor patient outcomes. DBF4 plays a critical role in DNA replication and participates in various biological functions, making it an attractive target for cancer treatment. However, its significance in ccRCC has not yet been explored. Methods We utilized external datasets and bioinformatics analyses to investigate the significance of DBF4 in ccRCC. We analysed its expression patterns, prognostic and diagnostic value, and potential mechanisms. We subsequently validated our findings through an immunohistochemistry (IHC) assay of ccRCC clinical samples. We further investigated the impact of DBF4 on the progression of ccRCC cells. Various assays, including assessments of cell proliferation, apoptosis, the cell cycle, cell migration and invasion, and colony formation, and xenograft tumor models were subsequently performed following to the knockdown of DBF4 expression via shRNA. Results Bioinformatics analyses revealed that DBF4 is significantly overexpressed in ccRCC tissues compared with adjacent normal tissues. This overexpression was confirmed by IHC analysis of 75 pairs of clinical ccRCC tumor and adjacent tissues. Kaplan-Meier analysis revealed that high DBF4 expression was associated with a significantly lower five-year overall survival rate. Moreover, DBF4 expression was identified as an independent risk factor in multivariate Cox regression analysis. GO and KEGG pathway enrichment analyses revealed a substantial enrichment of terms associated with cell division, whereas gene set enrichment analysis (GSEA) revealed correlations between increased DBF4 expression and the activation of cell cycle-related pathways. Subsequent in vitro and in vivo experiments demonstrated that DBF4 knockdown in ccRCC cells not only suppressed proliferation and migration in vitro but also significantly inhibited tumor growth in xenograft mice by arresting the cell cycle at the G1/G0 phase, which was mediated by the inhibition of MCM2 phosphorylation and cyclin D1 and CDK4 expression. Conclusion The current study revealed that DBF4 overexpression is a significant factor associated with malignant features and poor prognosis in patients with ccRCC. Therefore, it was proposed that DBF4 could serve as a novel potential prognostic biomarker and molecular target for ccRCC. Clinical trial number Not applicable.